Development of skills in working with official documents in military diplomatic relations in cadets - Norboyeva Madina Diyor qizi (Genius Publishing Group, 2023)
This article explores the importance of developing skills in working with official documents in military diplomatic relations for cadets. It outlines the methods employed in such training, presents the results of skill development, discusses their significance, and offers conclusions and suggestions for improving this crucial aspect of military education.
Keywords: Cadets; official documents; military diplomacy; skills